Technical change, workers' endowment and returns and investments in firm-level training: evidence from Thailand - Yamauchi, Futoshi; Poapongsakorn, Nipon; Srianant, Nipa (International Centre for the Study of East Asian Development, 2004)
This paper examines determinants of investments in and returns to training with focus on technical changes and workers' productive endowment, using employee panel data in Thai manufacuring industries. Empirical findings demonstrate significant returns to both on the job and off the job training in first-difference fixed effectestimation of wage equations, controling technological change and workers' ability (endowment) which are shown to influence, but differentially, both training investments and the returns. More specifically, first, technical change induces on-the-job training; controling technical change, returns to on the job training areeven larger. Second, controling workers' unobserved productive endowment, both returns to on-the-job and off-the-job training are found to be significantly positive, and endowment is substitutable to off-the-job training. Policy implications on training and education policies are discussed in detail.